2014
DOI: 10.1186/1756-0500-7-558
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs and perceptions about the causes of breast cancer: a case-control study

Abstract: BackgroundAttributions of causality are common for many diseases, including breast cancer. The risk of developing breast cancer can be reduced by modifications to lifestyle and behaviours to minimise exposure to specific risk factors, such as obesity. However, these modifications will only occur if women believe that certain behaviours/lifestyle factors have an impact on the development of breast cancer.MethodThe Breast Cancer, Environment and Employment Study is a case-control study of breast cancer conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
64
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 52 publications
(78 reference statements)
6
64
0
1
Order By: Relevance
“…Women with breast cancer tend to attribute the illness to many factors, including: psychological factors and stress, trauma (knocks or bruises) in the breast, religious causes, exposure to chemicals and electronic equipment, bacterial or viral infection and poor luck (Thomson et al 2014). Nevertheless, there is insufficient epidemiological evidence to support such causal attributions (McKenna et al 1999).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Women with breast cancer tend to attribute the illness to many factors, including: psychological factors and stress, trauma (knocks or bruises) in the breast, religious causes, exposure to chemicals and electronic equipment, bacterial or viral infection and poor luck (Thomson et al 2014). Nevertheless, there is insufficient epidemiological evidence to support such causal attributions (McKenna et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…A case-control study (Thomson et al, 2014) conducted with 1109 women with breast cancer and 1633 without the illness carried out in Australia between 2009 and 2011 found that the most common reasons given by non-cancer were related to family or hereditary factors (77.6 %), followed by factors related to lifestyle, such as poor diet and smoking (47.1 %) and environmental factors such as food with pesticides (45.4 %). In the group of women with breast cancer, emotional factors, such as stress were the most cited (46.3 %), followed by factors associated with lifestyle (38.6 %) and physiological factors (37.5 %).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, understanding how women attribute causes to cancer is relevant for health promotion, including a greater awareness and dissemination of early detection programs, treatment and development of public policies. It is known that the causal attributions can affect the response of women to messages in relation to health and the adoption of behaviors related to prevention, including screening tests (13) . Given the above, the aim of this study was to examine and compare the causal attribution of CC in two groups of women: those with Cervical Cancer and those without Cervical Cancer.…”
Section: Introductionmentioning
confidence: 99%